Prinsip Keadilan Dalam Interaksi Belajar Mengajar: (Kajian Al-Qur’an Surat Al-Maidah Ayat 8) - Atina Labiibah; Ngarifin Shidiq; Muhammad Saefullah (Jurnal Budi Pekerti Agama Islam, 2024)
This article discusses the principle of justice in teaching and learning interactions (study of Qur'an Surah Al-Maidah Verse 8) and aims to find out the principle of justice in learning interactions according to Al-Qur'an Surah Al-Maidah verse 8 and the relevance of justice in teaching and learning interactions according to Al-Qur'an Surah Al-Maidah verse 8. Data is taken from books or scientific works related to the problems to be discussed in the form of tafsir, the Qur'an, education and justice. Tafsir tahlili is used to interpret the verses of the Qur'an by describing all aspects contained in the verses being interpreted and explaining the meanings included in it according to the expertise and tendency of the mufassir who interpreted the verses. Surah Al-Maidah verse 8 explains about a fair attitude in an effort to uphold the truth because of Allah SWT. In the educational process, educators have a very important role to provide teaching and learning to students. Learners deserve a proper education. Education that does not look at the social level that students have. As a mandate holder, educators are very responsible for educating their students fairly and thoroughly and educating as well as possible and paying attention to humanism values. Because later in time will be held accountable for his work.